Stepwise or couple antenatal carrier screening for cystic fibrosis?: women's preferences and willingness to pay. Issue 4 (April 1995) - Miedzybrodzka, Z; Semper, J; Shackley, P; Abdalla, M; Donaldson, C
Abstract : Several antenatal cystic fibrosis carrier screening trials have offered women testing by either the stepwise or the couple method. In this study, both approaches were described to women attending an antenatal clinic, who were then asked which method they preferred. An estimate of the value to women of each type of test was also ascertained using a "willingness to pay" (WTP) method. Of 450 women, 279 (62%) preferred stepwise screening, 117 (26%) preferred couple screening, and 54 (12%) had no preference. Mean WTP for stepwise screening was 19 pounds (95% CI 17.50 pounds-20.50 pounds), and that for couple screening was 18 pounds (95% CI 16.50 pounds-19.50 pounds). The majority of women preferred stepwise screening although the average WTP for each method was similar.